2012
DOI: 10.1007/s10585-012-9475-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of signal transducer and activator of transcription 3 (STAT3) correlates with Her-2 status, carbonic anhydrase 9 expression and prognosis in esophageal cancer

Abstract: The signal-transcriptional factor signal transducer and activator of transcription (STAT3) is overexpressed in various tumor entities and promotes tumor progression and metastasis. The tyrosine-kinase receptor Her-2 was shown to activate STAT3-expression and is overexpressed in a subtype of esophageal cancer (EC). STAT3 also regulates carbonic anhydrase IX (CAIX) expression in vivo, promoting IL-6-dependent tumor invasion.Tumor-tissue from 324 patients with EC and 45 patients with precursor lesions were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Furthermore, CA IX expression correlates with various prognostic factors, including c-ErbB2 [124,125], epidermal growth factor receptor, c-ErbB2 and MUC-1 [126], EGFR and matrix metalloproteinase MMP-9 [102], osteopontin and CD44 [127], p53 and p300 [128], estrogen receptor, progesterone receptor, bcl-2, p53, c-ErbB2 and Ki-67 [114], cyclin E, cyclin A2, Ki-67 [111], lysyl oxidase, ephrin A1, galectin-1 [117], Slug [51], manganese superoxide dismutase [129], etc. Elevated CA IX protein in triple-negative breast cancer is associated with a BRCA1 mutant signature and loss of BRCA1 function [53].…”
Section: Ca IX Distribution In Tumors and Correlations With Clinical mentioning
confidence: 99%
“…Furthermore, CA IX expression correlates with various prognostic factors, including c-ErbB2 [124,125], epidermal growth factor receptor, c-ErbB2 and MUC-1 [126], EGFR and matrix metalloproteinase MMP-9 [102], osteopontin and CD44 [127], p53 and p300 [128], estrogen receptor, progesterone receptor, bcl-2, p53, c-ErbB2 and Ki-67 [114], cyclin E, cyclin A2, Ki-67 [111], lysyl oxidase, ephrin A1, galectin-1 [117], Slug [51], manganese superoxide dismutase [129], etc. Elevated CA IX protein in triple-negative breast cancer is associated with a BRCA1 mutant signature and loss of BRCA1 function [53].…”
Section: Ca IX Distribution In Tumors and Correlations With Clinical mentioning
confidence: 99%
“…It has been shown that upregulated expression of STAT3 is associated with more malignant behavior of tumor cells and worse prognosis in a variety of human malignancies, e.g., cancers of the breast, prostate, ovary, lung, head and neck, esophagus, and brain [53,54,55,56,57,58,59,60,61]. In pancreatic cancer, STAT3 was shown to regulate angiogenesis and metastasis [62] and to promote cellular proliferation by accelerating G1/S-phase progression [63].…”
Section: Jak/stat Signaling In Different Cancer Typesmentioning
confidence: 99%
“…CA9 was reported to be an endogenous sensor to HIF-1 activity (27) and CA9 inhibitors were more potent in 3D culture due to the regions of hypoxia (28). One report demonstrated a strong correlation in vivo between pSTAT3 and CA9 expression and postulated that the regulation of CA9 by STAT3 could be important in invasion through IL-6 signaling (29). Both of these transcription factors are regulated by APE1/Ref-1, so the impact of APE1/Ref-1 redox activity on HIF1 activity as well as CA9 expression was evaluated in PDAC following exposure to hypoxia.…”
Section: Introductionmentioning
confidence: 99%